2019
DOI: 10.1186/s42836-019-0009-1
|View full text |Cite
|
Sign up to set email alerts
|

Do we really need a surgery for hip fractures in elderly patients? Mortality rate and influencing factors

Abstract: Background: Hip fractures are associated with notable mortality rates in elderly patients. The purpose of the study was to evaluate the mortality rate and influencing factors associated with mortality in the elderly patients with hip fractures. Methods: Between October 2000 and December 2009, 807 elderly patients with hip fractures were enrolled in this study. There were 197 men and 610 women. The mean age at injuries were 78 years (range, 65-99 years). The fractures consisted of 390 femoral neck fractures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
1
8
1
Order By: Relevance
“…In our study, patients were allowed to fully weight-bear on POD1 and nearly 70% of them returned to their pre-injury activity level at the latest follow-up. Additionally, the mortality rate was 3.2% (1/31), considerably lower than that reported in previous literature [ 20 ]. These promising results might be attributable to the early mobilization allowed by our surgery.…”
Section: Discussioncontrasting
confidence: 55%
“…In our study, patients were allowed to fully weight-bear on POD1 and nearly 70% of them returned to their pre-injury activity level at the latest follow-up. Additionally, the mortality rate was 3.2% (1/31), considerably lower than that reported in previous literature [ 20 ]. These promising results might be attributable to the early mobilization allowed by our surgery.…”
Section: Discussioncontrasting
confidence: 55%
“…This result is similar to the result of the Spanish sample in our study. In addition, some studies have shown that having more than 3 common comorbidities are risk factors that lead to the death of patients in one year [37]. In this study, we have found that the proportion of patients with 3 or more types of comorbidities is signi cantly higher in Spain than in China.…”
Section: Discussionsupporting
confidence: 45%
“…In high-income injuries, paediatric forearm fracture are typically treated non-operatively with good outcomes [ 27 ]. On the other hand, 85% of proximal femoral fractures (hip) are treated operatively in high-income countries as they are associated with poor quality of life and function if treated non-operatively [ 28 – 30 ], but our study showed only 15% of proximal femoral fractures were treated operatively. Further studies are needed to clarify the reasons behind these severe injuries not being surgically fixed in LICs.…”
Section: Discussionmentioning
confidence: 74%